Modulation effect of Herbal extracts on the antibacterial activity of Tetracycline - Bayor MT, Annan K, Gbedema SY, Adu F, (Journal of Medical Biomedical and Applied Sciences, 2014)
As part of our ongoing study to screen local herbs for their possible usefulness in chemotherapy of infectious diseases, we assessed extracts from sixteen herbs for their antimicrobial properties and their influence on the activity of tetracycline. The minimum inhibito-ry concentrations (MIC) of tetracycline against Staph. aureus, B. subtilis, P. aeruginosa, E. coli and S. typhi were determined alone and in the presence of sub-inhibitory concentrations of the extracts by the KirbyâBauer agar diffusion method of antibacterial assay. Twelve of the extracts potentiated the antibacterial activity of tetracycline against at least one of the test bacteria